Sustained improvement in left ventricular function after successful coronary angioplasty. Issue 5 (May 1990) - Perry, R A; Singh, A; Seth, A; Flint, E J; Hunt, A; Murray, R G; Shiu, M F
Abstract : The short and long term effects of successful percutaneous transluminal coronary angioplasty on left ventricular function, at rest and on exercise were investigated in 49 patients. Thirty-four had had no previous infarction (group 1) and 15 had (group 2). Technetium-99m gated blood pool images were obtained at rest and during exercise before, six weeks after, and a mean of fifteen months after successful angioplasty. Before angioplasty the mean (SD) ejection fraction fell significantly on exercise in both groups from 58 (10)% to 53 (13)% in group 1 and from 48 (10)% to 40 (16)% in group 2. This change was paralleled by a worsening wall motion score (from 0.6 (0.4) to 1.6 (1.2) in group 1 and from 2.3 (1.9) to 3.3 (2.4) in group 2). Six weeks after the procedure there was little change in resting ejection fraction but it increased significantly on exercise (to 62 (11)% in group 1 and to 53 (13)% in group 2). There was a concomitant significant improvement in the exercise wall motion score (to 0.4 (0.6) in group 1 and to 1.8 (1.1) in group 2). This improvement in exercise ejection fraction and wall motion was maintained at later follow up with no significant deterioration in either variable and a clearly sustained improvement in ejection fraction (60 (10)% in group 1 and 51 (10)% in group 2) and wall motion score (0.2 (0.2) in group 1 and 1.3 (0.8) in group 2) compared with values before angioplasty. The initial improvement in left ventricular function on exercise after successful angioplasty was maintained for at least 9-24 months both in patients with previous myocardial infarction and in those without.